PERLINDUNGAN HUKUM BAGI PEKERJA OUTSOURCING DI KOTA MEDAN BERDASARKAN UU No. 13 TAHUN 2003 - Joshua Dewantoro Simatupang; Margaretha E.M. Pandia; Vebri Valentine (MIZAN, Jurnal Ilmu Hukum, 2021)
Outsourcing is a work system, namely the existence of one company which provides certain work abilities to other companies where they need it. The State of Indonesia as a state of law makes a law to protect every implementation and the parties in this outsourcing work system, the Law is Law no. 13 of 2003 concerning Manpower. The enactment of the Manpower Law has not been able to provide legal protection for parties in the outsourcing work system, especially for workers. This study aims to determine the form of outsourcing in Indonesia, determine the effect of the implementation of the Indonesian outsourcing work system and also find out the legal protection for outsourcing workers based on the Decision: No. 191/Pdt.Sus-PHI/2017/PN Mdn. The information sorting method is complemented by additional information sorting strategies, in particular by utilizing library information which is sourced from court decisions, laws and regulations, journals and mass media. The conclusion of this test, that re-evaluation is the right approach of the company in terms of business capabilities, but workers who do the work should not lose their rights which have been guaranteed by the relevant laws and guidelines. In terms of being identified with the situation of Decision No. 191/Pdt.Sus-PHI/2017/PN Mdn in accordance with the Manpower Law, it is the commitment of the management to terminate workers who are still working for a certain period of time to pay remuneration for the remainder of the agreement.